English Mere Christian Hermeneutics: Transfiguring What It Means to Read the Bible Theologically: By Kevin Vanhoozer - Wu, Calvin (Indonesian Journal of Theology, 2025)
A book review of Mere Christian Hermeneutics: Transfiguring What It Means to Read the Bible Theologically.